2023
DOI: 10.3390/ijerph20032705
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Framework for On-Demand Caesarean Section in Romania

Abstract: Background: Caesarean section rates have continued to trend upward in most countries, including Romania, creating a number of economic challenges. In the public health system, there is no regulation for performing Caesarean sections on demand; it is often done unlawfully, and in private hospitals, it is a real business. Thus, this study aims to investigate the budgetary impact at a hospital level and the profit per procedure by introducing on-demand caesarean sections for a fee. Methods: This study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Noteworthy, C-section rate in Romania (44.1% in 2017) was estimated by the Eurostat as the second highest in the European Union ( 39 ), reaching as high as 80% in private clinics ( 40 ). C-section rates of 60.7% ( 41 ) and 64% ( 42 ) were found in two studies performed in two large maternity hospitals in Romania. It is also acknowledged that nowadays in Romania more women elect C-section delivery regardless of a medical recommendation based on prejudgments, fear, or misbeliefs amplified by low level of medical understanding ( 40 – 42 ).…”
Section: Resultsmentioning
confidence: 95%
“…Noteworthy, C-section rate in Romania (44.1% in 2017) was estimated by the Eurostat as the second highest in the European Union ( 39 ), reaching as high as 80% in private clinics ( 40 ). C-section rates of 60.7% ( 41 ) and 64% ( 42 ) were found in two studies performed in two large maternity hospitals in Romania. It is also acknowledged that nowadays in Romania more women elect C-section delivery regardless of a medical recommendation based on prejudgments, fear, or misbeliefs amplified by low level of medical understanding ( 40 – 42 ).…”
Section: Resultsmentioning
confidence: 95%
“…Eurostat data on the percentage of cesarean births in EU countries in 2017 revealed the highest rates in Cyprus (54.8% of all live births being performed via cesarean section), followed by Romania (44.1%), and Bulgaria (43.1%) [37]. A recent paper by Petre et al reported even higher rates in Romania, ranging from 53.6% to 60.7% [38]. Various factors, both personal and external, contribute to this excessive use of cesarean sections.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients insured in the state health system pay a monthly contribution from their salary, a significant percentage of them prefer to pay extra to the private health service for certain services (4). The analysis of the data shows that this phenomenon is mainly due to the shorter waiting time in private clinics compared to the state system, the medical services (which are estimated by the patients to be superior in the private environment), the possibility for the patient/legal guardian to choose the doctor (in a private clinic), and the possibility to perform laboratory tests quickly, especially in the private environment compared to the state system.…”
Section: Discussionmentioning
confidence: 99%